Improving the Cooperative level of Preschool Children During the Intra vena Injection Through Virtual Reality Cartoon Education - Arief, Yuni Sufyanti; Ximenes, Regina Soares Da Costa; Ulfiana, Elida (International Journal of Psychosocial Rehabilitation, 2020)
Preschoolers who are hospitalized have higher anxiety and fear reactions, especially when given an intravenous injection which is included in an invasive procedure, therefore a distraction method is needed, such as an educational cartoon virtual reality. The purpose of this study was to determine the effect of educational cartoon virtual reality on the cooperative level of preschool children during intravenous injection procedures. A quasi experiment method with pretest-posttest control group design was used. The sample was 34 children aged 4-6 years who underwent treatment in one of the public hospitals in Atambua, who were selected by purposive sampling. The independent variable was educational cartoon virtual reality while the cooperative level was the dependent variable. Data were collected by using cooperative level observation sheet then analyzed using Wilcoxon sign rank test and Mann Whitney u test with significance p≤0.05. The results of this study showed that the cooperative level of the treatment group increased with a significance value of p=0.000, while the control group was not significant with a value of p=0.340. There was a difference in the cooperative level of preschool children in the control and treatment groups after being given the intervention of virtual reality educational cartoon with a significance value of p=0.000. Educational cartoon virtual reality can be used as an alternative distraction and educational media in improving the cooperation of preschool children during the intravenous injection procedure. Further researchers can develop educational cartoon virtual reality interventions in terms of content/topics, age targets, or other types of invasive procedures in hospitals or health centers